Analisis Kelayakan Investasi Smart Homestay Bu Ai Di Situs Wisata Gunung Padang - Ashila Paradika, Shafa; Wibisono, Masodah (Eastasouth Institute, 2024)
The research aims to assess the investment feasibility of Bu Ai's smart homestay. Bu Ai's smart homestay investment feasibility assessment is one of the Matching Fund Grant programs. The subject of this research is Bu Ai's Smart Homestay Business located in Kp.Gunung Padang, Karyamukti Kec.Campaka Kab.Cianjur West Java. This research was conducted for 5 months starting from August-December. The data used in this study are primary data. The methods used in this research are Payback Period, Net Present Value, Profitability Index and Internal Rate of Return. The results found that the feasibility assessment using PP, NPV, PI, & IRR is not feasible. However, at this time the investment is still accepted due to other factors including the location of the homestay which is located in the Gunung Padang site tourism area which has the potential to continue to increase.